2011
DOI: 10.1017/s0950268811000513
|View full text |Cite
|
Sign up to set email alerts
|

Costs of illness due to endemic cholera

Abstract: Summary Economic analyses of cholera immunization programmes require estimates of the costs of cholera. The Diseases of the Most Impoverished programme measured the public, provider, and patient costs of culture-confirmed cholera in four study sites with endemic cholera using a combination of hospital- and community-based studies. Families with culture-proven cases were surveyed at home 7 and 14 days after confirmation of illness. Public costs were measured at local health facilities using a micro-costing meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 19 publications
3
41
1
3
Order By: Relevance
“…as well as direct and indirect economic costs (lost wages for patient and caretaker, value of time away from school for children). Poulos et al (2008) found average private COI to be US$5.3 for cases in children and US$6.5 for adult cases. Because our model does not distinguish between adult and child cases, we use a weighted average of US$5.5 because incidence is six times higher in children .…”
Section: Cost-of-illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…as well as direct and indirect economic costs (lost wages for patient and caretaker, value of time away from school for children). Poulos et al (2008) found average private COI to be US$5.3 for cases in children and US$6.5 for adult cases. Because our model does not distinguish between adult and child cases, we use a weighted average of US$5.5 because incidence is six times higher in children .…”
Section: Cost-of-illnessmentioning
confidence: 99%
“…Poulos et al (2008) found average public COI to be approximately US$15 for child cases and US$16 for adult cases. We use US$15 for our analysis.…”
Section: Cost-of-illnessmentioning
confidence: 99%
“…38 Several studies have evaluated the cost of cholera illness in developing countries. [40][41][42][43] Economic burden: high income country A MEDLNE search found no studies evaluating the economic burden of cholera in developed countries. .…”
Section: Economic Burden: High Income Countrymentioning
confidence: 99%
“…42 A hospitalized case incurred a mean total cost ranging from $31.5 (Bangladesh) to $205.7 (Indonesia) for all ages and $36.0 to $223.0 for children <5 y (2005 $US); total outpatient costs of illness were $28.1 for all ages and $23.5 for children under 5 y in Indonesia. 42 This study prospectively followed cases (both community and hospital cases) and included extensive and comprehensive costs.…”
Section: Economic Burden: High Income Countrymentioning
confidence: 99%
See 1 more Smart Citation